Torsional Necrosis of an Output Loop Internal Hernia After Roux-en-Y Choledochojejunostomy: A Case Report - Huang, Chao; Ning, Zhikun; Zhu, Zhengming (Frontiers in Surgery, 2019)
Ultra-short bowel syndrome (USBS) refers to a clinical condition characterized mainly by severe diarrhea and nutritional disorders caused by the residual small intestine length less than 30 cm [1]. After Roux-en-Y choledochojejunostomy, the output loop herniated from the back of the anti-reverse peristalsis loop, resulting in intestinal torsion and necrosis and leading to this rare case of internal hernia. Patients with torsion often show severe abdominal pain and persistent aggravation, but this symptom lacks specificity, making it easy to be misdiagnosed. Acute intestinal torsion and necrosis often lead to large-scale small bowel resection, resulting in USBS. We report a case of torsional necrosis of an output loop internal hernia after Roux-en-Y choledochojejunostomy, providing certain reference for diagnosis and management of such cases.